Pengaruh edukasi mobilisasi dini dengan media audiovisual dalam dukungan keluarga pada pasien post operasi - Maula, Inayah; Sunarsih, Sunarsih; Rihiantoro, Tori (JOURNAL of Public Health Concerns, 2025)
Background: Based on interviews with postoperative patients in the digestive surgery room at General Ahmad Yani Regional Hospital, many are reluctant to undergo early mobilization due to a lack of family support. This lack of family knowledge regarding postoperative patient care, particularly regarding early mobilization, leads to a lack of family support for early mobilization, which can increase the risk of postoperative complications. Purpose: To determine the effectiveness and influence of education using audiovisual media on early mobilization in postoperative patients. Method: This activity was conducted at General Ahmad Yani Regional Hospital, Metro, Lampung Province, from April 15 to May 15, 2025. This activity was a quasi-experimental study using a non-equivalent control group design with a posttest only approach. The population in this study were postoperative patients undergoing general anesthesia at General Ahmad Yani Regional Hospital, Metro, Lampung Province. Using a non-probability sampling technique, 30 respondents were selected as the control group and 30 respondents as the experimental group. The experimental group received an intervention in the form of education using audiovisual media to implement early mobilization. Results: Data showed that the majority of control group respondents (18 (60.0%) received good family support, while the majority of experimental group respondents (26 (86.7%) received good family support. The p-value was 0.041 with an OR of 4.333. The p-value was 0.041 (p<0.05) and the odds ratio (OR) was 4.333, indicating that families of patients who received audiovisual education were 4.33 times more likely to provide good support. Conclusion: The audiovisual-based educational approach not only increased knowledge but also influenced family attitudes and behaviors in responding to postoperative patient needs, thus providing better motivation for early mobilization. Suggestion: It is hoped that future activities can create more engaging educational videos so that this audiovisual education method can have a more significant effect. Keywords: Audiovisual; Early mobilization; Family support; Postoperative patients Pendahuluan: Berdasarkan wawancara pasien pasca operasi di ruang bedah digestif RSUD Jend. Ahmad Yani banyak yang enggan untuk melakukan mobilisasi dini karena kurangnya dukungan dari keluarga. Minimnya pengetahuan keluarga tentang perawatan pasien pasca operasi terutama tentang mobilisasi dini pasien post operasi menyebabkan kurangnya dukungan keluarga terhadap anggota keluarga dalam pelaksanaan mobilisasi dini pasca operasi yang dapat meningkatkan risiko terjadinya komplikasi pasca operasi. Tujuan: Untuk memgetahui efektifitas dan pengaruh edukasi dengan media audiovisual dalam pelaksanaan mobilisasi dini pada pasien post operasi. Metode: Kegiatan ini dilaksanakan di RSUD. Jend. Ahmad Yani Metro Provinsi Lampung pada 15 April – 15 Mei 2025. Kegiatan ini adalah quasy eksperiment (ekperimen semu) dengan pendekatan non-equivalent control group design with posttest only. Populasi pada penelitian ini adalah pasien post operasi dengan general anestesi RSUD. Jend. Ahmad Yani Metro Provinsi Lampung. Dengan menggunakan teknik non-probability sampling, mendapatkan 30 responden sebagai kelompok kontrol dan 30 responden sebagai kelompok eksperimen. Kelompok eksperimen diberikan intervensi berupa edukasi dengan menggunakan media audiovisual dalam menerapkan mobilisasi dini. Hasil: Mendapatkan data bahwa sebagian besar responden kelompok kontrol yang mendapatkan dukungan keluarga dalam kategori baik sebanyak 18 (60.0%), sebagian besar juga untuk responden yang mendapat dukungan keluarga kelompok eksperimen dalam kategori baik sebanyak 26 (86.7%), dan mendapatkan pValue=0.041 dengan nilai OR=4.333. Dengan mendapatkannya nilai p=0.041 (p<0.05) dan nilai Odds Ratio (OR) sebesar 4.333, yang berarti keluarga dari pasien yang menerima edukasi dengan media audiovisual memiliki kemungkinan 4.33 kali lebih besar untuk memberikan dukungan yang baik. Simpulan: Pendekatan edukatif berbasis audiovisual tidak hanya meningkatkan pengetahuan, tetapi juga memengaruhi sikap dan perilaku keluarga dalam merespons kebutuhan pasien pasca operasi sehingga memberikan motivasi yang lebih baik pada tindakan mobilisasi dini. Saran: Diharapkan untuk kegiatan selanjutnya dapat mengkreasikan video edukasi menjadi lebih menarik lagi sehingga metode edukasi dengan media audiovisual berupa video ini dapat memberikan efek yang lebih signifikan.